Place, space and object oriented learning methods within the Library - Jenni Paton (University of Huddersfield Press, 2022)
A practical reflection of the impact of Escape Rooms style games both physical and digital on the way HE students experience the Library, examined through the lens of place oriented learning and digital learning theories with a particular focus on accessibility and the inclusion of historically excluded groups.We focus on two Escape Room style events, one physical, one digital developed by frontline library staff to support the induction of students in a University Library setting and reflect upon the aims, development and impact of the events.